Modelling irrigation and fertiliser use for chlorophyll production - Pérez-Ortolá, Marta; Daccache, Andre; Knox, Jerry W. (Wiley, 2016)
Chlorophyll is a natural coloring extract used extensively in the food and pharmaceutical industries. In Europe, most chlorophyll is produced commercially from rainfed grassland production in eastern England. This paper describes a biogeochemical modeling study to assess the potential yield benefits associated with switching from rainfed to irrigated production. The research is in response the impacts of recent summer droughts on yield coupled with risks regarding climate change, rainfall reliability and long-term viability of rainfed production. The Denitrification-Decomposition model was calibrated and validated using multiple field data (n = 47) from 2000 to 2009 for a tall fescue grass (Festuca arundinacea) to simulate a range of irrigation and fertilizer management regimes on yield (annual and individual yield per cut). For chlorophyll production, a schedule combining 300 mm year−1 irrigation with 300 kg N ha−1 was shown to provide the highest average yield (an uplift of +62% above current levels). Switching from rainfed to irrigated production could also potentially halve (54%) current levels of fertilizer application. The implications for reducing environmental impacts from nitrate leaching are discussed.
Keywords: Crop model; grass; irrigation scheduling; water; yield